Patient-Centered Research: Hypertension in Patients with Vascular Disease: Is Control Adequate? - Simmons, C (Blackwell Science Inc, 2000)
PURPOSE: Many patients with uncomplicated hypertension do not achieve adequate blood pressure control. To determine whether the development of vascular disease results in improved hypertension management, we investigated the blood pressure control in a cohort of patients with existing vascular disease (abdominal aortic aneurysm [AAA], carotid artery stenosis [CAS], peripheral vascular disease [PVD]). METHODS: We performed a retrospective chart review of all patients admitted to our tertiary care center in 1998 for elective surgery for either AAA, CAS or PVD. Charts were abstracted for demographic information, the prevalence of hypertension, and blood pressure control on admission and discharge. Discharge levels of blood pressure were used to determine the prevalence of normotension and each stage of hypertension, from mild (Stage 1) to severe (Stage 3). RESULTS: There were 186 patients who underwent one of the 3 procedures in 1998 (AAA n = 78; CAS n = 65; PVD n = 43). Forty-three percent of the group had an existing diagnosis of hypertension, with the highest prevalence in the CAS subgroup (49%). The average admission blood pressure was 144/79 and decreased to 135/73 at discharge (p < 0.001). Over half (53%) of the patients with a history of hypertension had systolic hypertension (SH) at discharge, and almost 40% of patients without a prior diagnosis of hypertension had SH at discharge. Discharge blood pressure levels for the entire cohort are shown below. Despite the high prevalence of hypertension at discharge, hypertension was listed as a medical problem in only 22% of discharge summaries. CONCLUSION: Hypertension contributes significantly to the development of vascular disease. The results of our study suggest that even in the presence of vascular disease, hypertension control is not optimal. Although the retrospective nature and the study setting limit the generalizability of the results, it is clear that there is room for improvement in the management of hypertension in this group of high risk individuals.